Salt transport in Songkhla Lake - Pornpinatepong, S. (Songklanakarin Journal of Science and Technology (SJST), 2005)
Salinity surveys in 1997 revealed that in the dry season salinity in Thale Sap Songkhla, Thale Sap and Thale Luang reached the maximum values of 30, 11 and 5 ppt, respectively. Among the complex system of the lake, Khlong Pak Ro showed a complicate seawater transport with a maximal salinity of 20 ppt. Incomplete mixing with a stratification at a depth of 2-3 m occured. The difference in salinity between the surface and the bottom was about 3 ppt. A vertically-averaged salt transport model was employed to simulate the salinity intrusion in the lake. The results showed quite good agreement with the observation. The model depicted a sharp drop of the water level at the entrance from the Gulf into the lake. The tidal energy then spread widely in Thale Sap Songkhla and continuously decreased to Thale Luang. The predicted salinity indicated that salt transport in the lake is governed by tide and water losses from the lake. Tidal movement generated a quasi-steady state of salinity in three months. The water losses for two months caused the salinity to rise 5.8 ppt/1 mm/day loss (~13 m3/s)at Pak Ro. With a loss of 2.3 mm/day (~28 m3/s), the whole lake became brackish in three months. The salt entered the lake mainly through Khlong Luang, and only for 13 percent through Ao Thong Ben.